2014
DOI: 10.1007/s40670-014-0041-2
|View full text |Cite
|
Sign up to set email alerts
|

Educating Junior Doctors to Reduce Requests for Laboratory Investigations: Opportunities and Challenges

Abstract: We assessed the impact of educational strategies to reduce requests by junior medical officers for pathology laboratory investigations. We demonstrated a noticeable reduction in test requests following a campaign to encourage the use of a case-based online simulation tool. However, achieving an adequate participation rate and sustaining change were significant challenges.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Most investigations within the hospital system are ordered by junior doctors. It has been previously postulated that the critical period to teach doctors judicious requesting is within the first 2 years of practice . Education, audit and feedback are all effective in teaching; however, given the frequency of rotation through various specialties, it can be difficult to have continuity .…”
Section: Discussionmentioning
confidence: 99%
“…Most investigations within the hospital system are ordered by junior doctors. It has been previously postulated that the critical period to teach doctors judicious requesting is within the first 2 years of practice . Education, audit and feedback are all effective in teaching; however, given the frequency of rotation through various specialties, it can be difficult to have continuity .…”
Section: Discussionmentioning
confidence: 99%
“…Ritchie et al 4 concluded that encouraging junior doctors to use an e-learning tool such as iNvestigate reduced laboratory test costs by A$66,000 in six clinical departments over a sixweek period in a major tertiary hospital. In a study by Seguin et al 5 , the ordering of blood gas analysis and electrolytes in the ICU was reduced by 22% by providing information about the costs of tests.…”
Section: Introductionmentioning
confidence: 99%